Changes of myocardial dysfunction and injury biomarkers over chemotherapy for multiple myeloma: difficulties in laboratory data interpretation - E. V. Fomina; S. A. Kardovskaya; D. A. Budanova; P. A. Markin; S. A. Appolonova; A. S. Lishuta; Yu. N. Belenkov; I. S. Ilgisonis (Столичная издательская компания, 2023)
Aim. To study the changes of the levels of cardiac biomarkers (N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity troponin I (hsTnI)) in patients with newly diagnosed multiple myeloma (MM) during programmatic treatment with bortezomib (VCd regimen).Material and methods. This prospective pilot study included patients with a newly diagnosed MM (n=30), who were scheduled for a cycle of chemotherapy including a proteasome inhibitor (bortezomib). All patients underwent standard laboratory (complete blood count, biochemical tests, serum protein electrophoresis), electrocardiography, echocardiography, as well as the level of specific laboratory markers of myocardial dysfunction (NT-proBNP) and injury (hsTnI) was determined immediately before treatment, after 3 and 6 cycles of chemotherapy.Results. The mean age was 63,8±10 years with a slight predominance of men (56,7%, n=17). The patients initially had an increased level of NT-proBNP (316 [75,9; 602,6] pg/mL) with its decrease to 144,0 [102,3; 294,0] pg/ml after 3 cycles and to 109,2 [59,9; 344,5] pg/ml after 6 cycles of chemotherapy. At the MM onset, the mean hsTnI values were 0,06 [0,03; 0,49] ng/mL, whereas after 3 and 6 chemotherapy cycles it accounted for 0,02 [0,01-0,68] and 0,65 [0,02; 1,51] ng/ml, respectively, with the normal range of less than 0,1 ng/ml. Despite this, no statistical significance has been obtained. There were no clinical and/or laboratory signs of heart failure, ischemia, or other non-cardiac causes of elevated NT-proBNP levels in this cohort. Multivariate regression analysis revealed the following significant factors influencing the initial hsTnI level: paraprotein, hemoglobin and erythrocyte sedimentation rate (ESR). The resulting regression model was characterized by a strong correlation (r=0,702, p<0,001).Conclusion. MM and its pathogenetic features such as paraproteinemia may be challenging for NT-proBNP and hsTnI levels assessment in group of interest before treatment. An unreliable assessment of these markers before chemotherapy may lead to incorrect baseline cardiovascular risk stratification and make it difficult for a cardiologist/cardio-oncologist to choose proper management strategy.